The influence of cognitive level on the guaranteed behavioral response of landless farmers in the context of rural revitalization–An empirical study based on partial least squares structural equation modeling - Lu, Yangjie; Dong, Hao; Wang, Huanyuan (Frontiers in Psychology, 2022)
With the continuous acceleration of urbanization and agricultural modernization in China, the trend of concentration of rural land transfer is irreversible. For landless farmers, the absence of land guaranteed function inevitably gives rise to the substitution effect of other guaranteed methods. And the subjective preferences exhibited by farmers in making guaranteed behavior decisions can be quantitatively described as guaranteed behavioral responses (GBRs). Based on the analytical framework of distributed cognitive theory, this paper adopts the validated factor analysis method of structural equation modeling to quantitatively study the cognitive basis and behavioral responses of landless farmers’ guaranteed behavior by combining the survey data of rural households in typical rural areas of Wuhan urban area. The study shows that the GBRs of landless farmers are significantly influenced by the cognitive level. “Locality power,” “cultural power,” and “personal power” are the main, important, and effective cognitive levels that influence farmers’ GBRs, respectively. Policy-based protection occupies a dominant position in the rural social guaranteed system, savings-based protection still plays an important function in rural areas, and market-based protection has greater development potential.